The Celtic myths that shape the way we think - Williams, Mark 1980- (Thames & Hudson, 2021)
The events of Celtic mythology have been retold and reinterpreted for millennia, shapeshifting and reshaped by authors and artists who have given their own vivid characters a rich and powerful afterlife. Williams focuses on the myths that have had the greatest cultural impact, and explores the multiple meanings they have inspired in the ages since their inception. -- adapted from jacket
"First published in the United Kingdom in 2021 by Thames & Hudson Ltd."--Title page verso
Keywords: Kelten; Mythologie; Mythology, Celtic; Folklore / British Isles; Folklore; Europe / British Isles